Research on the Transformation of College Teachers’ Classroom Roles in the "Internet+" Era - Xiao, Linlin (Journal of Theory and Practice of Contemporary Education, 2023)
University teachers are an important component of China's education system and the main battlefield for cultivating talents. With the advent of the "Internet" era, the classroom roles of traditional university teachers are clearly no longer able to adapt to the current situation of the times, and the transformation of classroom roles is the trend. On the basis of analyzing the traditional roles of university teachers, this article reanalyzes the new roles of university teachers in the new era and summarizes the ways to transform the roles of university teachers.